2016
DOI: 10.1093/jmammal/gyw104
|View full text |Cite
|
Sign up to set email alerts
|

Does acclimation to contrasting atmospheric humidities affect evaporative water loss in the South American subterranean rodentCtenomys talarum?

Abstract: Water conservation is challenging for terrestrial life since water is continuously lost through respiration, excretion, and cutaneous evaporation. Total evaporative water loss (TEWL) is an important component of the water budget. In general, TEWL is mainly determined by biophysical mechanisms, such as ambient temperature (T a) and humidity. However, it has also been suggested that TEWL can be actively regulated in the short term to confront environmental conditions and be further modified by development and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 58 publications
(96 reference statements)
0
2
0
Order By: Relevance
“…Other subterranean rodents only spend a certain amount of time underground (Schleich & Antenucci 2009; Baldo et al . 2016; Šumbera et al . 2020), unlike the Spalax species; however, these animals may experience more drastic O 2 fluctuations (frequent switches between normoxia and hypoxia).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other subterranean rodents only spend a certain amount of time underground (Schleich & Antenucci 2009; Baldo et al . 2016; Šumbera et al . 2020), unlike the Spalax species; however, these animals may experience more drastic O 2 fluctuations (frequent switches between normoxia and hypoxia).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that Spalax ehrenbergi can survive 3% O 2 for 8 h without significant deleterious effects, while similar-sized rats were found to die after 2-4 h (Avivi et al 1999). Other subterranean rodents only spend a certain amount of time underground (Schleich & Antenucci 2009;Baldo et al 2016;Šumbera et al 2020), unlike the Spalax species; however, these animals may experi-ence more drastic O 2 fluctuations (frequent switches between normoxia and hypoxia). Studies on subterranean rodents have generally been limited to the adaptive mechanisms in blind mole rats and naked mole rats because of their unique life history and spectacular hypoxia tolerance (Malik et al 2012;Peterson et al 2012;Grimes et al 2014;Schmidt et al 2017).…”
Section: Introductionmentioning
confidence: 99%